Role And Community in Constitutional Right to Meet Education for Street Children - Agatha Jumiati; Waluyo Slamet Pradoto (Universitas Slamet Riyadi, 2020)
Children as the next generation of quality nation absolutely have the right to obtain proper and adequate education. The Indonesian government together with the community is obliged to realize adequate education for Indonesian children. This study aims to determine community participation in efforts to fulfill the constitutional rights of education for street children. This research is a descriptive empirical legal research using primary and secondary data and qualitative data analysis. In Indonesia, street children cannot get an education because they live on the streets or are often called street children. On the other hand the constitutional responsibility of the state is one of them is seeking education for all Indonesian children. The limited ability of the state to fulfill these responsibilities has encouraged the community to participate in realizing the fulfillment of the right to education for Indonesian children, especially children traveling.